IMPLEMENTASI SISTEM PENGENDALIAN MUTU PADA KANTOR AKUNTAN PUBLIK ABC DENGAN BASIS VALUE - Rika Yulia Rahmawati; Theresia Dwi Hastuti (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2023)
The purpose of this research is to finding out how Sistem Pengendalian Mutu (SPM) is applied to a Kantor Akuntan Publik (KAP), how KAP redesigns SPM  implementation based on standards and values and aims to see how the application of SPM affects audit quality. This study uses all individuals in the KAP ABC as informants, including one Partner, one Supervisor and six Auditor Staff. Research data was collected by interviewing all informants. Research data was analyzed manually and supported by Nvivo software tools to improve the quality of analysis. The results of this study indicate that in KAP ABC there are values (independent value, confidentiality value, family value and cohesive value) that are well internalized, but the implementation of SPM in KAP ABC has not been carried out optimally resulting in less than optimal audit quality.